Food Quality and Safety Systems. - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
A Training Manual on Food Hygiene and the Hazard Analysis and Critical Control Point (HACCP) System